2023
DOI: 10.3390/molecules28073132
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Expression of a Therapeutic Protein Serratiopeptidase

Abstract: Serratiopeptidase is a clinical therapeutic protein for the treatment of human diseases such as arthritis, bronchitis, and thrombosis. Yet production of this protein in a heterologous host (e.g., Escherichia coli) is difficult due to the issue of protein insolubility and the requirement of laborious refolding procedures. Cell-free protein synthesis (CFPS) systems, derived from crude cell extracts, are effective platforms for the expression of recombinant proteins in vitro. Here, we report a new method to produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Since protease enzymes have bivalent cations like zinc and calcium as essential co-factors within their structure, the loss in enzyme activity can be due to some competitive/noncompetitive interactions [ 30 ]. It is also known that calcium can protect the enzyme from autolysis, and by introducing additional amounts of Ca 2+ ions, the activity of SER can be increased [ 45 ]. Indeed, our experiments revealed that the enzyme activity can be increased by two times by adding Ca 2+ to the buffer (SER/CaCl 2 mass ratio1:1).…”
Section: Resultsmentioning
confidence: 99%
“…Since protease enzymes have bivalent cations like zinc and calcium as essential co-factors within their structure, the loss in enzyme activity can be due to some competitive/noncompetitive interactions [ 30 ]. It is also known that calcium can protect the enzyme from autolysis, and by introducing additional amounts of Ca 2+ ions, the activity of SER can be increased [ 45 ]. Indeed, our experiments revealed that the enzyme activity can be increased by two times by adding Ca 2+ to the buffer (SER/CaCl 2 mass ratio1:1).…”
Section: Resultsmentioning
confidence: 99%
“…CFPS systems have been widely developed for in vitro protein synthesis with the advantages of time‐saving, easily manipulable, microscale, high‐throughput, and portable. [ 48 ] CFPS has also inspired the multidiscipline research fields, including genetic engineering, [ 49 ] metabolic engineering, [ 50–53 ] high‐throughput screening, [ 54 ] pharmaceutical production, [ 55,56 ] and education. [ 57,58 ] Therefore, a powerful chassis is essential for establishment of CFPS system.…”
Section: Resultsmentioning
confidence: 99%
“…CFPS systems have been widely developed for in vitro protein synthesis with the advantages of time-saving, easily manipulable, microscale, high-throughput, and portable. 45 CFPS has also inspired the multidiscipline research fields, including genetic engineering, 46 metabolic engineering, 47−50 high-throughput screening, 51 pharmaceutical production, 52,53 and education. 54,55 Therefore, a powerful chassis is essential for CFPS system establishment.…”
Section: Establishment Of the Probiotic Ecn-based Cfps Systemmentioning
confidence: 99%